Pendidikan Islam dan Pembentukan Sosial Budaya Umat: Analisis Pemikiran KH. Hasyim Asy’ari dan Relevansinya di Era Kontemporer - Siti Nurrahmatin Ni’mah; Muhammad Arif Syihabuddin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Islamic education constitutes a fundamental foundation in shaping character, morality, and the socio-cultural order of the Muslim community, whose relevance continues to be tested amid the dynamics of contemporary change. This study aims to examine the role of Islamic education in the formation of Muslim socio-cultural life and to analyze the contemporary relevance of KH. Hasyim Asy’ari’s educational thought. This research employs a qualitative library research method, focusing on conceptual and theoretical analysis of relevant literature, particularly Adab al-‘Alim wa al-Muta‘allim and other supporting academic sources. Data analysis was conducted using a thematic analysis approach to identify key themes related to Islamic educational concepts, values of adab and morality, teacher–student relationships, and the socio-cultural implications of education. The findings reveal that KH. Hasyim Asy’ari’s educational thought emphasizes adab and moral character as the core foundation of education, rejects the dichotomy between religious and secular knowledge, and promotes the integration of intellectual, moral, and spiritual dimensions. Islamic education, from his perspective, plays a significant role in shaping a civilized, moderate, and ethical Muslim society. The relevance of KH. Hasyim Asy’ari’s thought in the contemporary era lies in its holistic and contextual educational paradigm, which remains responsive to the challenges of globalization, moral degradation, and the evolving socio-cultural dynamics of modern society. Keywords: Adab, Contemporary Relevance, Islamic Education, KH. Hasyim Asy’ari Socio-Cultural